Influence of estrous cycle and gestation on cardiovascular system of bitches - Almeida, Vivian T.; Uscategui, Ricardo A.R.; Camacho, Aparecido A.; Sousa, Marlos G.; Santos, Victor J.C.; Maronezi, Marjury C.; Vicente, Wilter R.R. [UNESP]; Feliciano, Marcus A.R. [UNESP] (Elsevier, 2018)
The purpose of this study was to evaluate the consequences of the estrous cycle and gestation on the cardiovascular system of bitches evaluated through echocardiographic assessment. Fifteen healthy pregnant bitches aged 2 to 6 years and weighing 8.8 ± 2.5 kg were included in the study. Heart rate and blood pressure were clinically evaluated. M-mode, spectral, and tissue Doppler-echocardiography assessments were performed during the anestrous and estrous stages, every 15 days during pregnancy (15, 30, 45, and 60 days), and 45 days postpartum. The data for evaluated variables were submitted for statistical analysis. Heart rate (P = 0.286) and systolic blood pressure (P = 0.686) were not changed as a result of pregnancy or estrus, while ejection fraction (P = 0.0016) and fractional shortening (P = 0.00004) changed. The variables transmitral flow, isovolumetric relaxation time, aortic and pulmonary flow, and some variables related to myocardium movement obtained via tissue Doppler assessment varied (P < 0.05) among the reproductive periods studied. In conclusion, gestation resulted in changes in echocardiography variables, and consequently, on maternal hemodynamics, with myocardial contractility increasing during pregnancy, resulting in greater systolic efficiency and ventricular compliance.
Keywords: Canine; Cardiac function; Morphophysiology; Pregnant